The Idea of a Liberal Theory : a Critique and Reconstruction. - Johnston, David, 1951- (Princeton University Press, 2001)
Liberalism, the founding philosophy of many constitutional democracies, has been criticized in recent years from both the left and the right for placing too much faith in individual rights and distributive justice. In this book, David Johnston argues for a reinterpretation of liberal principles he contends will restore liberalism to a position of intellectual leadership from which it can guide political and social reforms. He begins by surveying the three major contemporary schools of liberal political thought--rights-based, perfectionist, and political liberalism--and, by weeding out their we.
Keywords: Liberalism.; Philosophy -- Political.; Political science -- Political Ideologies -- General.; Libéralisme.; liberalism.; POLITICAL SCIENCE -- Political Ideologies -- General.; PHILOSOPHY -- Political.; Political science; Philosophy; Liberalism